The critical role of diet, exercise, and sleep in shaping the gut microbiota of children with idiopathic short stature: a Retrospective study - Zeng, Qin; Zhu, Jun; Hu, Yanling; Su, Shaoyu; Chen, Jing (Frontiers in Immunology, 2025)
ObjectivesTo investigate the gut microbiota in children with varying degrees of idiopathic short stature (ISS) and to examine the relationship between their intestinal microbiota and lifestyle factors, including diet, exercise, medication, sleep, and psychological state.MethodsA retrospective study involving 58 ISS children was conducted from May to October 2022. Lifestyle data were collected using questionnaires. Fecal samples were analyzed using 16S rRNA gene sequencing to assess microbiota diversity and composition. LEfSe analysis identified differential bacterial communities between ISS-2SD and ISS-3SD groups (LDA score ≥ 2.5). Spearman correlation analysis explored the relationship between microbiota diversity, dominant taxa, and lifestyle factors, visualized in a heatmap.ResultsNo significant differences in alpha diversity of intestinal microbiota were observed among children with varying degrees of short stature at the ISS, but differences were noted in the dominant microbiota. The ISS-2SD group had Leptotrichiaceae and Sneathia as predominant members, whereas the ISS-3SD group was dominated by Lachnoclostridium, Thermous_scotoductus and Thermoles. Correlation analysis revealed that microbiota diversity was linked to diet, especially legume consumption (Shannon index: r=0.372, P=0.004; Simpson index: r=0.379, P=0.003). At the genus level, Prevotella was positively correlated with beverage intake (r=0.262, P=0.047) and sleep quality (r=0.324, P=0.013), while Ezakiella was negatively correlated with meat intake (r=-0.297, P=0.024), Other genera exhibited significant correlations with diet, exercise, and sleep.ConclusionChildren with varying degrees of short stature exhibited differences in their dominant intestinal microbiota. Diet, exercise, and sleep appear to be significant factors influencing these microbial changes in ISS children.